A critical review of the thermophysical properties and applications of carbon-based hybrid nanofluids in solar thermal systems - Borode, Adeola; Tshephe, Thato; Olubambi, Peter (Frontiers in Energy Research, 2025)
This review focuses on the potential of carbon-based hybrid nanofluids to enhance the performance of solar thermal energy systems. Solar thermal technology is pivotal in transitioning towards renewable energy sources, offering sustainable alternatives to conventional fossil fuels. However, traditional heat transfer fluids (HTFs) often exhibit limitations in thermal conductivity (TC), which hinders the overall efficiency of solar collectors. The introduction of nanofluids, particularly hybrid nanofluids that combine two or more types of nanoparticles, has emerged as a promising solution to address these challenges. Among various nanomaterials, carbon-based materials such as graphene and multi-walled carbon nanotubes (CNTs) have garnered significant attention due to their exceptional thermal properties. This review critically analyses the thermal and rheological characteristics of carbon-based hybrid nanofluids and their effects on solar thermal applications, including flat-plate collectors and parabolic trough collectors. The unique synergy achieved by integrating carbon-based nanoparticles with metallic nanoparticles results in improved TC, enhanced heat transfer rates, and greater stability compared to single-component nanofluids. Despite the notable advantages, challenges such as increased viscosity and the need for long-term stability under operational conditions remain pertinent. Future research directions should prioritize optimizing nanoparticle concentrations, exploring cost-effective alternatives, and investigating the long-term performance of hybrid nanofluids in dynamic environments. The findings of this review underscore the transformative potential of carbon-based hybrid nanofluids in improving the efficiency and effectiveness of solar thermal systems, thus supporting the broader adoption of renewable energy technologies. This exploration is essential for advancing solar thermal applications and addressing the ongoing challenges of energy sustainability and efficiency in the face of growing global energy demands.